Korelasi Kadar Serum Albumin terhadap Massa, Kekuatan Otot dan Performa Fisik pada Usia Lanjut di Poliklinik Geriatri Rsmh Palembang - Nur Riviati; Legiran; Irsan Saleh; Taufik Indrajaya; Surya Dharma; Muhammad Reagen; Fifi Yuniarti; Syafran Rasidi; Fadhyl Zuhry Lubis; Bima Indra (Bahasa Indonesia, 2023)
Introduction: Sarcopenia is a common problem found in the elderly. It is characterized by loss of muscle mass, muscle strength, and/or low physical performance. Currently, there’s little research on the association between serum albumin and muscle mass, muscle strength, and physical performance in the elderly, especially in Indonesia. This study aimed to find the correlation between serum albumin and muscle mass, muscle strength, and physical performance in the elderly. Method: A cross-sectional study was conducted from July 2022 to December 2022 towards elderly patients (>60 years) from the geriatric polyclinic at RSUP Moh. Hoesin Palembang. Serum albumin was examined for its correlation with muscle mass, muscle strength, and physical performance using Spearman’s test. Result: 41 elderly patients were included in this study (mean age 70.75 ± 7 years, 56.1% women). Correlation analysis showed that there’s a significant positive correlation between serum albumin with muscle strength (r=0.354, p=0.012) and a negative correlation with physical performance (r=-0.5, p <0.001). In comparison, there was no significant correlation between serum albumin and muscle mass (r=- 0.05, p=0.367). Conclusion: Muscle strength and physical performance have a significant correlation with serum albumin in the elderly. Therefore, even in the normal range, lower serum albumin is closely related to sarcopenia in the elderly. Key Words: albumin, muscle mass, muscle strength, physical performance, sarcopenia.